2012
DOI: 10.1371/journal.pone.0037037
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Inequalities in the Use of Postnatal Care in India

Abstract: ObjectivesFirst, our objective was to estimate socio-economic inequalities in the use of postnatal care (PNC) compared with those in the use of care at birth and antenatal care. Second, we wanted to compare inequalities in the use of PNC between facility births and home births and to determine inequalities in the use of PNC among mothers with high-risk births.Methods and FindingsRich–poor ratios and concentration indices for maternity care were estimated using the third round of the District Level Household Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 21 publications
8
81
0
1
Order By: Relevance
“…The 12 articles from India were all original research articles and eight were carried out predominantly among rural populations, 10-17 two related to urban settings 18,19 and two analysed national data. 20,21 This high proportion of studies on the rural population might be related to the facts that in India 74% of the population resides in rural areas and 70% of rural births are at home, assisted by family members or traditional birth helpers. With one exception, 17 all 12 articles mention, if not focus on, the high maternal and neonatal mortality rates in India.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 12 articles from India were all original research articles and eight were carried out predominantly among rural populations, 10-17 two related to urban settings 18,19 and two analysed national data. 20,21 This high proportion of studies on the rural population might be related to the facts that in India 74% of the population resides in rural areas and 70% of rural births are at home, assisted by family members or traditional birth helpers. With one exception, 17 all 12 articles mention, if not focus on, the high maternal and neonatal mortality rates in India.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A UK study 27 examined the effect of caseload midwifery practices on a culturally diverse group and one Australian study 4 compared the obstetric intervention rates and birth outcomes between Australian and overseas born. Also included in the review were ten literature reviews 6,7,[27][28][29][30][31][32][33][34] (Table 3), one book chapter, 22 and three scholarly, but non-research articles; a clinical paper on the Migrant Health Guide in UK, 35 a report from the Lancet 36 and To explore the links between multiple deprivations and use of maternal services 21 Singh an opinion piece in Australian Midwifery News by an Indian midwife. 37 No research article was found specifically exploring Indian women's childbearing experiences in Australia.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…There are numerous evidence from India that show that the public health system in India treats its clients according to their socio-economic conditions (Singh et al, 2012a;Singh et al, 2012b;Malhotra and Do, 2012). There is also evidence to show that the public health personals provide services to their clients based on their own perceptions and beliefs rather than based on the needs of the clients (Pallikadavathet al, 2004;Matthews et al, 2001;Dhandapany et al, 2008).All these reduce the effectiveness of the public health services in India.…”
Section: Discussionmentioning
confidence: 99%
“…The regional differences in India highlight socioeconomic differences and differential access to maternal and child health services (Singh et al, 2012;Pathak et al, 2010;Pallikadavath et al, 2004). Education and household wealth are particularly strong predictors of antenatal care use in India.…”
Section: Discussionmentioning
confidence: 99%